Capital Expenditure as a Moderating Variable in the Influence of Regional Original Income on GRDP - Suwarno (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
ABSTRACT This research is a quantitative study with an explanatory approach, namely an approach that makes the three studies mentioned repeatedly the mainstay for developing ongoing research. The data used in this study are secondary data that researchers obtained from reports from the East Java Central Statistics Agency over a period of ten years from two thousand fourteen to two thousand twenty-four. The result in this article show that each hypothesis used in this article can be accepted. In the first hypothesis in this study, the Regional Original Income variable can have a positive relationship direction and a significant influence on GRDP. This is because the P-Values ​​in the third table of the Path Coefficient above are positive and below the significance level of 0.05, namely 0.011. These results are in line with a number of previous studies, namely (S, 2023); (Saleh, 2020) & (Rasu et al., 2019). In the next hypothesis, the Capital Expenditure variable can also strengthen the influence of the Regional Original Income variable on GRDP. This is because something similar, namely the P-Values, is positive and below the significance level of 0.05, namely 0.000. Thus, it can be concluded that the first and second hypotheses in this study can be accepted.